Celsr1 and Celsr2 exhibit distinct adhesive interactions and contributions to planar cell polarity - Basta, Lena P.; Sil, Parijat; Jones, Rebecca A.; Little, Katherine A.; Hayward-Lara, Gabriela; Devenport, Danelle (Frontiers in Cell and Developmental Biology, 2023)
Cadherin EGF LAG seven pass receptor (Celsr) proteins 1-3 comprise a subgroup of adhesion GPCRs whose functions range from planar cell polarity (PCP) signaling to axon pathfinding and ciliogenesis. Like its Drosophila ortholog, Flamingo, mammalian Celsr1 is a core component of the PCP pathway, which, among other roles, is responsible for the coordinated alignment of hair follicles across the skin surface. Although the role of Celsr1 in epidermal planar polarity is well established, the contribution of the other major epidermally expressed Celsr protein, Celsr2, has not been investigated. Here, using two new CRISPR/Cas9-targeted Celsr1 and Celsr2 knockout mouse lines, we define the relative contributions of Celsr1 and Celsr2 to PCP establishment in the skin. We find that Celsr1 is the major Celsr family member involved in epidermal PCP. Removal of Celsr1 function alone abolishes PCP protein asymmetry and hair follicle polarization, whereas epidermal PCP is unaffected by loss of Celsr2. Further, elimination of both Celsr proteins only minimally enhances the Celsr1-/- phenotype. Using FRAP and junctional enrichment assays to measure differences in Celsr1 and Celsr2 adhesive interactions, we find that compared to Celsr1, which stably enriches at junctional interfaces, Celsr2 is much less efficiently recruited to and immobilized at junctions. As the two proteins seem equivalent in their ability to interact with core PCP proteins Vangl2 and Fz6, we suggest that perhaps differences in homophilic adhesion may contribute to the differential involvement of Celsr1 and Celsr2 in epidermal PCP.